ANALISIS PELAKSANAAN PENGAWASAN PERSEDIAAN BAHAN BAKU AMPLANG UNTUK MENUNJANG PROSES PRODUKSI PADA UKM NUR AISYAH DI MUARA BADAK - -, Akbar Noor (EKONOMIA, 2017)
Small and Medium enterprises is an important part in the economy of Indonesian. Small and medium enterprises have a good role to increase the speed of the economy. In practice every industry small and medium enterprises should have optimal inventory so that the production activities of a business running smoothly. Therefore control or supervision of raw material inventory should be done to avoid delays in the supply of raw material inventory. Error in determining the amount of capital for inventory would depress corporate profits. If the company held inventories are too large in comparison with the company’s needs it will increase the cost of maintenance and storage in warehouse, as well as the possibility of delays in the production process of the company, so it can reduce corporate profits. The purpose of this study to investigate the implementation of inventory supervision of raw materials in the production process on Small and Medium enterprises, Based on the analysis and discussion, the conclusions of this study are; (1) In a corporate or home industry supplies of raw materials is one of the most important assets in the company. (2) Booking the most economical raw material for fish is 79 kg each time a message. The frequency of booking must be done 7 times as much as 79 kg with a total cost of 75,000 Rupiah of Indonesian. (3) That inventories of raw materials can be controlled so that small and medium enterprises should perform reordering when inventory in warehouse or engine cooling as much as 4 kilograms.